2010
DOI: 10.1007/s11270-010-0325-0
|View full text |Cite
|
Sign up to set email alerts
|

Lime and Gypsum as Source Measures to Decrease Phosphorus Loss from Soils to Water

Abstract: Phosphorus (P) loss from agricultural soils to water is a major contributor to eutrophication. In an incubation experiment with five contrasting soils, lime and gypsum showed potential as source measures to decrease P loss risk, as assessed by water extractions. Soils were incubated with lime to achieve a target pH of 6.5 and with gypsum at equivalent Ca rates for 108 days. P was added (17 kg P ha −1 ) as KH 2 PO 4 in solution. Gypsum appears to have greater potential as a source measure, decreasing molybdate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 76 publications
4
52
1
1
Order By: Relevance
“…2. The increased P solubility with decreasing soil acidity has been explored in previous studies (Murphy and Stevens, 2010). The results indicated that the increasing of soil pH with biochar application may be important for the enhanced P availability.…”
Section: Influence Of Biochar On Phosphorus Availabilitymentioning
confidence: 98%
“…2. The increased P solubility with decreasing soil acidity has been explored in previous studies (Murphy and Stevens, 2010). The results indicated that the increasing of soil pH with biochar application may be important for the enhanced P availability.…”
Section: Influence Of Biochar On Phosphorus Availabilitymentioning
confidence: 98%
“…This results in a greater solubility of phosphorus due to the amount of ammonium ions, which is high in manure and slurry. According to Murphy and Stevens (2010), soil acidity neutralization with lime and gypsum to a pH of 6.5 results in decreasing molybdate-reactive P solubility by 14% to 56% and decreasing organic P by 10% to 53%.…”
Section: Effects Of Additives In Trench Backfillsmentioning
confidence: 99%
“…Until now, the majority of research in Ireland has focused on quantifying nutrient and, to a lesser extent, sediment losses from permanent grassland at laboratory- (Doody et al 2006;Murphy 2007;Murphy and Stevens 2010), plot/field- (Tunney et al 2007;Kurz et al 2000;Douglas et al 2007) and catchment-scales (Smith et al 1995;Scanlon et al 2004;Jordan et al 2005a;2005b;Smith et al 2005;Jordan et al 2007). Modelling of diffuse P loss from grassland catchments has also been undertaken by Jordan et al (2000), Daly et al (2002), Scanlon et al (2005) and Nasr et al (2007), with the aim of improving management strategies to minimise P loss.…”
Section: Research To Date On Sediment and P Lossmentioning
confidence: 99%